Analisis Pengaruh Tingkat Kesehatan Dan Tingkat Pendidikan Terhadap Tingkat Kemiskinan Di Indonesia Tahun 2017 - 2024 - Fernando, Eric; Samsuddin, M. Afdal (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This research seeks to examine how education and health levels influence poverty in Indonesia over the period from 2017 to 2024, utilizing quarterly data derived from interpolated annual figures. The study employs average years of schooling as a proxy for education, life expectancy as a measure of health, and the poverty rate to represent the level of poverty. A time series regression approach is applied, complemented by classical assumption tests including stationarity, normality, autocorrelation, heteroscedasticity, and multicollinearity to validate the robustness of the model. The findings reveal that education has a statistically significant negative effect on poverty, whereas health does not exert a meaningful impact. The adjusted R-squared value of 0.861 indicates that about 86.1% of the variation in poverty can be explained by the model's independent variables. These results highlight the critical role of enhancing educational access and quality as a strategic approach to poverty reduction in Indonesia. In developing countries, poverty is often influenced by limited access to education and basic health services, which hinders human capital development. Therefore, understanding the role of these factors is essential in designing inclusive and evidence-based public policies.